2010
DOI: 10.1007/s00134-010-2017-z
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative red blood cell transfusion and morbid outcome in uncomplicated cardiac surgery patients

Abstract: The data suggest a potential association between postoperative RBC transfusion and increased morbidity for cardiac surgery patients with low to moderate mortality risk profiles, adequate hemoglobin levels, and low bleeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
1
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 48 publications
8
71
1
11
Order By: Relevance
“…In a study conducted by Möhnle et al [15] in patients who had low risk of developing postoperative complications of cardiac surgery, it was observed that, despite the low risk patients who received blood transfusion had an increased risk of developing cardiac events, as well as an increase in surgical site infections. However, the authors report that the study's findings related to infectious, renal complications and hospital mortality should be carefully analyzed, mainly due to the fact that the group of transfused patients differs in several characteristics from the group that did not received blood transfusions in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Möhnle et al [15] in patients who had low risk of developing postoperative complications of cardiac surgery, it was observed that, despite the low risk patients who received blood transfusion had an increased risk of developing cardiac events, as well as an increase in surgical site infections. However, the authors report that the study's findings related to infectious, renal complications and hospital mortality should be carefully analyzed, mainly due to the fact that the group of transfused patients differs in several characteristics from the group that did not received blood transfusions in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell (RBC) transfusion is a frequent requirement after cardiac surgery, with 20.4% -48% occurring in the immediate postoperative period (1)(2)(3)(4) . Although it is lifesaving after cardiac surgery, RBC transfusion increases death rates from 5.4% to 13.4% in the long term, whereas median time to death is decreased from 4.7 years to 1.1 years (3) .…”
Section: Introductionmentioning
confidence: 99%
“…In the short term, RBC transfusion ≥4 units is an independent predictor of one-year mortality (2) . The risk for cardiac morbidity, different types of infections, acute respiratory distress syndrome and acute renal injury requiring dialysis or hemofiltration is also increased after RBC transfusion (1,4,6) .…”
Section: Introductionmentioning
confidence: 99%
“…Patients who undergo cardiac surgery tend to receive more blood transfusions than other surgery patients (WILLIAMS et al, 2011;MOHNLE et al, 2010;CAPRARO et al, 2007). According to Karkouti et al(2006), the incidence of blood transfusion during cardiac surgery varies from 27.0% to 92.0%.…”
Section: Discussionmentioning
confidence: 99%